2020
DOI: 10.1186/s12864-020-6597-x
|View full text |Cite
|
Sign up to set email alerts
|

A completeness-independent method for pre-selection of closely related genomes for species delineation in prokaryotes

Abstract: Background: Whole-genome approaches are widely preferred for species delineation in prokaryotes. However, these methods require pairwise alignments and calculations at the whole-genome level and thus are computationally intensive. To address this problem, a strategy consisting of sieving (pre-selecting closely related genomes) followed by alignment and calculation has been proposed.Results: Here, we initially test a published approach called "genome-wide tetranucleotide frequency correlation coefficient" (TETR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 53 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…Horizontal gene transfer may yield a high ANI of ≥96% for even distantly related species, according to Additional file 4 in Zhou et al ( 2020 ). In this context, demarcating such species based merely on the ANI criterion may lead to incorrect conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Horizontal gene transfer may yield a high ANI of ≥96% for even distantly related species, according to Additional file 4 in Zhou et al ( 2020 ). In this context, demarcating such species based merely on the ANI criterion may lead to incorrect conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…However, almost all these methods except for FastANI suffer from a large amount of pairwise whole-genome comparisons. In an effect to address this obstacle, we proposed a strategy called “sieving,” the process of pre-selecting closely related (intraspecies and some closely related interspecies) pairs for subsequent genome-wide alignment and calculation (Zhou et al, 2020 ), and developed the method called “ frag ment te tranucleotide frequency correlation coefficient” (hereafter termed FRAGTE1) for it (Zhou et al, 2020 ). Our previous study shows that FRAGTE1 is completeness-independent, highly sensitive (~100%), and highly specific as well as with both highly reduced overall number of sieved pairs and highly improved runtime, compared with the “ tetra nucleotide frequency correlation coefficient” (TETRA), FastANI, and the alignment-based approaches such as 16S rRNA-based approach (Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Richter and Rosselló-Móra, 2009). However, it is computationally intensive to calculate ANI, since genomic comparisons are based on pairwise alignments and calculations (Zhou et al, 2020). Apart from this, a recent revision has argued against the accuracy of the threshold proposed by the authors as a universal microbial species delineation, substantial sampling and species redundancy was found to alter the results and found no evidence of a universal genetic boundary among microbial species currently annotated in the NCBI taxonomy (Murray et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We found that both sketching programs, Mash and Dashing, performed well for draft genomes without even altering the cutoff for the complete genomes analyzed. Mash has been previously reported to also perform well in whole metagenome comparisons (Dong et al, 2020) and to be very useful in fungal taxonomy (Gostinčar, 2020), along with many other promising applications (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%